Methodology of Monitoring and Evaluation of the Innovation Potential of Azerbaijan - Arzu Huseynova; Salifova Tarana (Informaciâ i Innovacii, 2018)
The article examines the existing systems for assessing the activities of organizations, a conceptual approach to the formation of a monitoring system for innovation, a methodology for assessing the scientic and technological complexes of economic zones of Azerbaijan.Issues of assessing the innovative development of economic zones are examined on the basis of statistical data, the impact of socio-economic conditions in economic zones on innovation potential.The monitoring system for evaluating the activities of organizations, mechanisms for improving the management of the innovative potential of subjects, and the structural scheme of the management system for innovation potential have been studied